Pengaruh Kemampuan Berpikir Kritis Dan Kemampuan Komunikasi Matematis Terhadap Kemampuan Pemecahan Masalah Matematis Materi SPLDV - Khoirunnisya, Rachael; Inggrid Yurike, Gabriella; Susanti, Elsa; Sari, Novita; Ilma Indra Putri, Ratu (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This research aims to investigate the relationship between critical thinking skills and communication skills on junior high school students' mathematical problem solving abilities. A total of 31 class VIII students were selected through simple random sampling as research subjects. To measure each ability, a test was carried out using essay questions which were then analyzed quantitatively using correlation and multiple regression analysis. From this research, the results obtained show that both the correlation between critical thinking and problem solving abilities and communication and problem solving abilities are both in the high category. The coefficient of determination test results obtained were 0.540, which means that the contribution of critical thinking abilities and mathematical communication skills together to problem solving abilities was 54%. Penelitian ini ingin menyelidiki hubungan kemampuan berpikir kritis dan kemampuan komunikasi terhadap kemampuan pemecahan masalah matematis siswa SMP. Sebanyak 31 siswa kelas VIII dipilih melalui simple random sampling sebagai subjek penelitian. Untuk mengukur masing-masing kemampuan dilakukan tes menggunakan soal uraian yang selanjutnya dianalisis secara kuantitatif dengan analisis korelasi dan regresi berganda. Dari penelitian ini didapati hasil bahwa baik korelasi antara kemampuan berpikir kritis dan keterampilan menyelesaikan masalah maupun kemampuan komunikasi dan keterampilan menyelesaikan masalah sama-sama berada pada kategori tinggi. Hasil uji koefisien determinasi diperoleh sebesar 0,540 yang maksudnya besarnya kontribusi kemampuan berpikir kritis dan kemampuan komunikasi matematis secara bersama-sama terhadap kemampuan pemecahan masalah yaitu sebesar 54%.